(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
Before looking at the importance of sociolinguistics, we should pay attention to the terms "internal" and "external" in sociolinguistics. If a society uses its own language of the nation and the state, it is an internal language, and if a society uses second and third languages besides its mother tongue, it is a foreign language.